Development of Local Instructional Theory on Parallelogram Topics Based on RME to Improve Mathematical Problem-Solving Skills - Endah Zulfah; Ahmad Fauzan; I Made Arnawa (Riviera Publishing, 2024)
The purpose of this research is to develop a local instructional theory on parallelogram material and examine the improvement of students' mathematical problem-solving skills by using local instructional theory. This research uses the Design Research method, which uses the Gravemeijer and Cobb development model and the Plomp model. The Plomp development model has three stages, namely, preliminary research, prototyping phase, and assessment phase. The research subjects were seventh-grade students of MTs N 5 Jambi City. Data analysis techniques in this study used Quantitative data were obtained through questionnaires, while qualitative data were obtained through observations, interviews, field notes, and final test questions. The results of this study indicate that the local instructional theory on the topic of RME-based parallelogram in class VII is valid. The learning design met the practical criteria based on the results of the questionnaires and interviews. Based on the final test conducted shows that the local instructional theory is already in the effective category. So, the learning flow produced is valid, practical and effective. The implication of this research is that the development of local instructional theory on RME-based quadrilateral material can significantly improve students' mathematical problem solving ability. This shows that through the right approach in learning design, as implemented in this study, the problem solving ability problems that students often experience can be overcome. Thus, this approach has the potential to be widely applied in improving the effectiveness of mathematics learning in schools.